P–455 Breast cancer recurrence in women with and without controlled ovarian stimulation for fertility preservation. Cohort study. (6th August 2021) - Pesce, R; Vinacur, A F; Taboada, V; Allemand, C; Marciano, S; Perman, G
Abstract: Study question: Do patients diagnosed with breast cancer who undergo ovarian stimulation for fertility preservation prior to chemotherapy have a higher risk of recurrence of the disease? Summary answer: There was no statistically significant difference in the hazard ratio for breast cancer recurrence in fertility preservation-stimulated women compared to non-stimulated ones What is known already: While many women with early breast cancer benefit from chemotherapy treatments in increasing disease-free survival, they are also at risk of permanent chemotherapy induced ovarian failure. Oocyte cryopreservation with an adapted protocol with letrozole may reduce the possible deleterious effect of the hyper estrogenic state during the controlled ovarian hyperstimulation (COH). Although fertility preservation in women diagnosed with breast cancer seems safe, the follow-up periods of most studies are short in time. In addition, follow-up data of COH before neoadjuvant chemotherapy in women with hormone negative tumor receptors is still scarce and briefly reported. Study design, size, duration: It was a retrospective cohort study, where 208 women with non-metastatic breast cancer were included. The recruitment period was from 01/01/2009 to 01/12/2019. The minimum follow-up period was 6 months, and the maximum, 130 months. Participants were divided into two cohorts, those who received controlled ovarian hyperstimulation prior to their cancer treatment and those who did not. Patients were followed until disease recurrence, death, loss to follow-up, or end of the study Participants/materials, setting, methods: Setting: university hospital in Buenos Aires, Argentina. We included women aged 18 to 45 years with a recent histological diagnosis of non-metastatic breast cancer who had to receive chemotherapy with gonadal toxicity. We excluded patients with a history of previous chemotherapy or radiotherapy for another cancer disease, or menopause. Follow-up was at least an annual clinical check-up and breast imaging. Cohorts were analysed using a Cox-proportional hazards model, adjusted for propensity score for receiving stimulation. Main results and the role of chance: We included 208 women, 39 in the COH group and 169 in the non-stimulated group (NSG). The only statistically significant difference was in age: median years 33.7 (interquartile range -IQR- 30.9 to 36.9) and 40.0 years (IQR 36.8 to 44.0), respectively. The median size of cancer nodules was 19.0 millimetres (IQR 10.0–30.0) and 17.0 (IQR 11.0–25.0), p 0.547; percentage of positive lymph nodes: 41.0% vs 39.3%, p 0.841; positive hormonal receptors: 84.6% vs 85.2%, p 0.925; percentage of neoadjuvant chemotherapy: 20.5% vs 11.4%, p 0.128. There were also no statistically significant differences regarding tumour stage, high Ki–67 labelling index, positive breast cancer genes (BRCA 1 or 2), and radiotherapy. Overall, 18.0% of patients had cancer recurrence in the COH group and 20.7% in the NSG (p 0.699). Crude cancer recurrence rates were similar: 5.96 per 100 patients/year (95%CI 2.84–12.50), and 4.65 per 100 patients/year (95%CI 3.34–6.47), respectively. The crude hazard ratio (HR), comparing the COH group vs the NSG was 1.32 (95%CI 0.58–2.97; p 0.507). The adjusted HR using a propensity score for receiving ovarian stimulation treatment was 1.08 (95%CI 0.39–2.98; p 0.887). Results were similar if adjusted for age, neoadjuvant chemotherapy, and other confounders. Limitations, reasons for caution: This was a single-center retrospective cohort study. There might be unknown or residual confounders that could influence results. Nevertheless, we accounted for treatment bias using a propensity score for ovarian stimulation. Results should be extrapolated with caution, especially in other non-university institutions and populations. Wider implications of the findings: This study provides new evidence on the safety of controlled ovarian stimulation in breast cancer patients prior to chemotherapy treatment, in a Latin American population. Letrozole continues to show safety and efficacy as an adapted protocol in breast cancer. Trial registration number: Not applicable